REVISIÓN TAXONÓMICA DEL GÉNERO SOLERVICENSIA BARR, 1979 (COLEOPTERA: CLERIDAE: KORYNETINAE) - Solervicens A., Jaime (Acta Entomológica Chilena, 2022)
A taxonomic revisión of the species ascribed to Solervicensia Barr, 1979, is made. Only two species are recognized: Solervicensia ovatus (Spinola, 1849) and S. basipennis (Pie, 1950). The following taxa are established as new synonyms of S. ovatus: Korynetes aeneus Philippi y Philippi, 1864, Lebasiella limbipennis Chevrolat, 1876, Lebasiella lineata Pie, 1950, Lebasiella rufwollis Pie, 1950, Lebasiella ruficollis var. sinuatelineata Pie, 1950, Lebasiella Duboulayi Pie, 1950 and the varieties of Lebasiella subanchoralis Chevrolat, 1976 (species previously synonymyzed with 5. ovatus by Schenkling, 1916): L. s. subinterrupta Pie, 1950, L.s. ininterrupta Pie, 1950, Ls. latemetallica Pie 1950, and L.s. apicalis Pie, 1950. A redescription of S. ovatus is provided.